Research on the failure of the induced draft fan's shaft in a power boiler. (April 2016) - Du, Jinfeng; Liang, Jun; Zhang, Lei
Highlights: In this paper, the failure investigation had been paid attention to the analysis of failure cases which ranged from material performance, equipment's design to service condition of equipment, and thus the preventive measures were developed in order to avoid the recurrence of the similar failure. Abstract: The failure of the induced draft fan's shaft in a power boiler was been analyzed. The performances of material applied satisfied the design requirement. The order torsional vibration showed anomaly at the shaft's smallest diameter for the design condition and the actual radius of that chamfer less than the design radius caused more significant stress concentration. The additive effect of the abnormal torsional vibration and the higher stress concentration induced the microcrack's initiation along the network pearlite's interface. The vibration and the alternating torsional loading in the induced draft fan's service led to crack growing along the different direction and fracture presenting the typical ratchet-like characteristic.